Little Red and the cat who loved cake - Lehman, Barbara (Houghton Mifflin Harcourt, 2021)
In this wordless picture book, a variation on the classic fairy tale, Little Red has baked a cake with her father and they set off for Grandma's house, but along the way they are trailed by a cat who loves cakes.